2022
DOI: 10.1002/mabi.202100435
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin and Dermatan Sulfate Bioinks for 3D Bioprinting and Cartilage Regeneration

Abstract: Cartilage is a connective tissue which a limited capacity for healing and repairing. In this context, osteoarthritis (OA) disease may be developed with high prevalence in which the use of scaffolds may be a promising treatment. In addition, three‐dimensional (3D) bioprinting has become an emerging additive manufacturing technology because of its rapid prototyping capacity and the possibility of creating complex structures. This study is focused on the development of nanocellulose‐alginate (NC‐Alg) based bioink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 65 publications
0
15
0
2
Order By: Relevance
“…Moreover, it was shown that CS-tyramine hydrogels have a good cytocompatibility and the enhanced proliferation of porcine auricular chondrocytes [ 12 ]. Furthermore, CS can regulate cartilage metabolism and has anti-inflammatory properties trough cross-linking tyramine groups [ 13 ]. Gelatin (Gel), another natural compound, also possesses tyramine groups that could help to mimic the macromolecular structure and features of ECM [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was shown that CS-tyramine hydrogels have a good cytocompatibility and the enhanced proliferation of porcine auricular chondrocytes [ 12 ]. Furthermore, CS can regulate cartilage metabolism and has anti-inflammatory properties trough cross-linking tyramine groups [ 13 ]. Gelatin (Gel), another natural compound, also possesses tyramine groups that could help to mimic the macromolecular structure and features of ECM [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…5). 51 Dermatan sulfate (DS), which is similar to ChS, has also been tried by adding to NC-Alg ink to improve its properties. DS and ChS have the same chemical make-up, however there are certain glucuronic acid residues in DS that go through an epimerization process to become iduronates.…”
Section: The Biomaterials Selection For 3d-printed Cte Scaffoldsmentioning
confidence: 99%
“…The test results showed that the CS addition could effectively improve the characteristics of the cellular activity and rheology of the bio-ink. Simultaneously, the biological scaffold prepared using sodium cellulose-alginate–CS can effectively promote cartilage differentiation, providing a new method for cartilage regeneration [ 66 ]. Sousa et al used Tetrazine–CS (TCS), 8-Arm polyethylene glycol-Norbornene (8A-PEG-N), and 4-Arm polyethylene glycol-Norbornene (4A-PEG-N) as materials to prepare TCS-A-PEG-N porous hydrogels.…”
Section: Classification Of Natural Biomaterialsmentioning
confidence: 99%